Raft-like osmium- and ruthenium-antimony carbonyl clusters - Li, Ying-Zhou (2015)
The higher nuclearity raft-like cluster Os6(CO)20(μ-SbPh2)2, 5-Os, was isolated from the base hydrolysis of Os3(CO)11(SbPh2Cl), 1-Os. The ruthenium analogue, viz., Ru6(CO)20(μ-SbPh2)2, 5-Ru, was obtained from the reduction of Ru3(CO)12, 7-Ru, with the benzophenone ketyl radical followed by treatment with SbPh2Cl. These clusters undergo facile ligand substitution reactions with two-electron donors to afford the mono- and disubstituted derivatives M6(CO)20-n(μ-SbPh2)2(L)n, (M = Ru or Os; n = 1 (8) or 2 (9); L = PMe3 (a), PPh3 (b), or tBuNC (c)).